PENDIDIKAN GIZI INFORMAL KEPADA PENJAJA MAKANAN UNTUK PENINGKATAN KEAMANAN PANGAN JAJANAN ANAK SEKOLAH DASAR (INFORMAL NUTRITION EDUCATION TO FOOD VENDORS FOR IMPROVING SAFETY OF STREET-FOODS SELLING AT PRIMARY SCHOOL) - Evy Damayanthi; Khusnul Khotimah; Eddy Setyo Mudjajanto; Cesilia Meti Dwiriani; Lilik Kustiyah (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2013)
ABSTRACT Street foods have an important role in contributing school children energy and nutriens need. Nationally, there is a serious problem on the safety of street food near schoool, therefore an effort is needed to overcome the problem. The objective of this study was to develop a simple model to solve the safety problem of street food near school. The study was conducted in two steps. The first step was done in 10 primary schools to determine the problem and to define the method of problem solving. One school with the worst food safety problem was selected as area of research. The second step was to implement the defined method into the selected primary school. Descriptive and inferensia analysis were applied in this study. Based on street food safety risk evaluation, the defined methods are nutrition extension and assistance to street food vendors in primary school SDN "D". Food vendors at SDN “D” were mostly (88.9%) male, with age between 18-40 years old. Their education background was elementary school (44.7%) and classified as poor (55.6%). Knowledge, attitudes, and practices of most food vendors after nutrition extention and assistance are better than before. Pearson correlation test showed a positive significant correlation between knowledge and food safety attitudes (p <0.05). Meanwhile, there is no significant correlation between nutrition knowledge and attitude (p> 0.05), nutrition and food safety knowledge, with food safety practice (p> 0.05), and nutrition and food safety attitude with food safety practices (p> 0.05). Overall, the nutrition and food safety extension and assistance have been effective in improving knowledge, attitudes and practices of the food vendor but it needed more extensive and periodical assistance to sustain the impatct. Keywords: food safety, street-food selling at primary school, nutrition extension ABSTRAK Makanan jajanan memberikan kontribusi yang penting bagi pemenuhan kebutuhan zat gizi bagi anak. Secara nasional ada persoalan serius terhadap masalah keamanan makanan jajanan anak sekolah dasar sehingga perlu diupayakan cara mengatasinya. Penelitian ini bertujuan untuk mengembangkan model sederhana upaya mengatasi masalah keamanan makanan jajanan anak sekolah. Penelitian dilakukan dalam dua tahap. Tahap pertama dilakukan di 10 sekolah dasar (SD) untuk menentukan masalah dan upaya yang akan dilakukan. Satu SD dengan masalah keamanan makanan jajanan yang terparah kemudian ditentukan sebagai lokasi. Pada tahap kedua, upaya yang telah dirumuskan, diterapkan pada SD terpilih. Data diolah secara deskriptif dan inferensia. Berdasarkan tinjauan terhadap resiko ketidakamanan makanan jajanan, upaya yang dilakukan adalah penyuluhan gizi dan pendampingan pada SDN “D”. Penjual makanan di SDN "D" sebagian besar laki-laki (88,9%) dengan kisaran usia 18-40 tahun, berpendidikan SD (44,7%) dan tergolong miskin (55,6%). Pengetahuan, sikap, dan praktek sebagian besar penjual makanan setelah dilakukannya pendampingan lebih baik daripada sebelumnya. Uji korelasi Pearson menunjukkan hubungan yang positif nyata antara pengetahuan dan sikap keamanan pangan (p <0,05). Sementara itu. tidak ada hubungan antara pengetahuan dengan sikap gizi (p> 0,05), pengetahuan gizi dan keamanan pangan dengan praktik keamanan pangan (p> 0,05), dan sikap gizi dan keamanan pangan dengan praktik keamanan pangan (p> 0,05). Secara keseluruhan penyuluhan sudah efektif meningkatkan pengetahuan, sikap dan praktek penjual makanan tentang gizi dan keamanan pangan namun diperlukan pendampingan yang lebih intensif dan berkala untuk menjamin keberlanjutannya. [Penel Gizi Makan 2013, 36(1):20-30] Kata Kunci: keamanan pangan, pangan jajanan anak sekolah, penyuluhan gizi